Environmental education at the service of wetlands conservation in Northeast of Algeria - Souhila Allaoua; Karima Sifi; Choukri Barour; Mohamed Benslama (My University, 2019)
Algeria by its geographical position, geological configuration and the diversity of its climate presents an important richness of national and international wetlands. However, due to lack of information and sensitization, these wetlands are being degraded both by anthropogenic activities and by their underexploitation or overexploitation in the context of the valorization of their natural products. Thus, the Algerian Ministry of Environment has created the Environment Houses, whose main missions are education, information and sensitization on the protection and conservation of the environment in general. In this context, a survey was conducted in a few schools at all levels in four cities in northeastern of Algeria (Annaba, El Tarf, Skikda, Souk-Ahras) to assess the importance of environmental education and sensitization in the preservation of wetlands. The results showed that schools sensitized through environmental education campaigns led by Houses of Environment, have more knowledge about wetlands and their preservation, compared to those not sensitized. Indeed, this study has highlighted the primary role of environment houses in environmental education and sensitization of the need to protect and enhance these wetlands